RETRACTED: EZH2-Mediated microRNA-375 Upregulation Promotes Progression of Breast Cancer via the Inhibition of FOXO1 and the p53 Signaling Pathway - Guan, Xin; Shi, Aiping; Zou, Yabin; Sun, Meiyang; Zhan, Yue; Dong, Yi; Fan, Zhimin (Frontiers in Genetics, 2021)
Breast cancer (BC) is the most common gynecologic tumor worldwide where aberrant expression of microRNAs (miRNAs) is frequently involved. Here, we evaluated the function of miR-375 on BC development and the molecules implicated. Differentially expressed genes between tumor and the paired normal tissues from BC patients were screened out by microarray analyses. miR-375 was abundantly expressed in BC tissues and cells, and it was correlated with poor prognosis of patients. Downregulation of miR-375 was introduced into BC cell lines MCF-7 and HCC1954, after which the viability, colony formation, migration and invasion was suppressed, while the apoptosis of cells was increased, and the xenograft tumors in nude mice was reduced as well. EZH2 increased methylation and phosphorylation of signal transducer and activator of transcription 3 (STAT3) and increased transcription activity of miR-375, while miR-375 directly targeted FOXO1. Either overexpression of EZH2 or downregulation of FOXO1 blocked the functions of anti-miR-375 in cells and animals. FOXO1 was found as an activator of the p53 signaling pathway. This study evidenced that miR-375 is an important oncogene in BC. EZH2 is an upstream regulator of miR-375 through mediating methylation of STAT3, while FOXO1 is a downstream target mRNA of miR-375 which activates the p53 signaling pathway to suppress BC development.